Analysis of the Projection of Primary School Needs in Sukamakmue District, Sabang Municipality in 2045 - Sinabang, Immanuel; Salsabila, Gadis; Sinaga, Putri; Lubis, Darwin Parlaungan; Permana, Sendi; Rahmadi, M Taufik; Arif, Muhammad (Jurnal Penelitian Geografi (JPG), 2024)
The availability of educational facilities, particularly at the elementary level, plays a crucial role in regional development. This study aims to: (a) evaluate the availability of existing elementary school facilities in Sukamakmue District, (b) analyze the projected needs for elementary school facilities in Sukamakmue District by 2045, and (c) recommend appropriate policies to address the future needs for elementary school facilities in the district. The research utilizes a combination of secondary data analysis and primary data obtained through interviews with key stakeholders in the Education Office. The findings indicate that the distribution of public elementary schools is relatively even across all villages in Sukamakmue District, with a total of 7 public elementary schools currently available. However, based on the population projection for 2045, Paya Seunura Village is expected to experience significant population growth, necessitating the addition of more elementary school facilities over the next 21 years. The projection for facility needs was calculated using a facility needs analysis, with the base year set between 2021 and 2045. In contrast, the other villages show declining population growth, suggesting that no additional facilities will be required. Keywords: educational facilities; availability; needs; elementary school